Exploring Risk of Posture and Musculoskeletal Disorders among Smartphone Addicted Youth: a Protocol Paper (International Journal of Occupational Safety and Health, 2024)
Introduction: Smartphones with rapid advancement in telecommunication technology causing high usage leads to addiction, especially among youth. Concerning health, smartphone addiction influences posture causing neck-shoulder pain. However, the mechanism of how smartphone addiction causes pain related to posture control is still doubtful. Anticipatory feed-forward motor control mechanism has proposed that smartphone usage is a static low-level activity influenced by muscle fatigue and discomfort. Therefore, this study aimed to explore neck-shoulder muscle fatigue, particularly at the upper trapezius about smartphone addiction behaviors and adopted posture while using smartphones among youth. This study aims to investigate the relationship between smartphone addiction, risk of posture and the relationship between trapezius muscle fatigue, and neck-shoulder pain among youth.Methods: A cross-sectional study design will be conducted through convenient sampling among students at secondary schools in Malaysia. The Smartphone Addiction Scale, Rapid Assessment Upper Limb, Nordic Musculoskeletal Questionnaire and Electromyogram will be used as outcomes tools.Discussion: This study investigates the risk of smartphones in terms of duration usage among adults. Fatigue over the upper trapezius muscle has not yet been investigated among youth which will provide fundamental findings on how faulty posture during smartphone usage might cause neck pain.